Image Encryption on Mobile Phone Using Super Encryption Algorithm - Emy Setyaningsih; Catur Iswahyudi (Institute of Advanced Engineering and Science, 2012)
This study aims to obtain the digital image encryption algorithm with a simple but secure process, fast and efficient computing resources. The algorithms developed in this study were super-encryption algorithm that combines two of cipher called Playfair cipher and the Vigenere cipher. To improve security, a keystream generator was used to randomize the order of the next key in Vigenere cipher. In order to evaluate performance, the proposed algorithm was measured through a series of tests. These tests were implemented with Matlab included visual test and histogram analysis, information entropy, encryption quality, correlation analysis, and also time analysis. The test results show that cipher image looks visually random.The image histogram of the plain image and cipher image also seen a significant difference between the two of them. Testing was also performed on mobile phones with Symbian and BADA operating system based on Java Micro Edition Programming. Trial results show that the algorithm was require less computational resources; with average time for image encryption is 3.76 seconds, and the average time for image decryption is 0.97 seconds. The new proposed image encryption scheme has satisfactory security which makes it a potential candidate for encryption of image data. Keywords: Image encryption, Vigenere cipher, Playfair cipher, Security test DOI: http://dx.doi.org/10.11591/telkomnika.v10i4.875